Malignant sacrococcygeal germ cell tumors in childhood: The Associazione Italiana Ematologia Oncologia Pediatrica (AIEOP) experience. Issue 3 (21st November 2020) - D'Angelo, Paolo; De Pasquale, Maria Debora; Barretta, Francesco; Affinita, Maria Carmen; Conte, Massimo; Dall'Igna, Patrizia; Di Cataldo, Andrea; Inserra, Alessandro; Provenzi, Massimo; Quaglietta, Lucia; Riccipetitoni, Giovanna; Spreafico, Filippo; et al.
Abstract: Purpose: To evaluate clinical features at diagnosis, prognostic factors, and outcomes of malignant sacrococcygeal germ cell tumors (SC‐GCTs) in patients enrolled in the Associazione Italiana Ematologia Oncologia Pediatrica (AIEOP) TCG 2004 protocol. Patients and Methods: A prospective analysis was conducted on all consecutive patients diagnosed with malignant SC‐GCTs between January 2004 and May 2017. Patients with stage I underwent surgery and subsequent surveillance, the others received pediatric cisplatinum‐etoposide‐bleomycin (pPEB) regimen and eventual deferred surgery. Results: Of 45 patients, 35 were females. Age at diagnosis ranged from 1 day to 3.6 years (median 1.6 years); 26 were stage IV. Of 38 patients who underwent surgery, pathology revealed yolk sac tumor (YST) in 27 and teratoma + YST/embryonal carcinoma in 11, while seven patients were diagnosed based on imaging and elevated levels of alpha‐fetoprotein (AFP). Of six patients approached with surgery, only one relapsed and was rescued with first‐line chemotherapy. Overall, 38 out of 45 achieved complete remission, three a partial remission, and four were resistant. Ten out of 41 patients who entered remission later relapsed and nine were rescued with a second‐line treatment. We observed a global failure percentage of 31% and a 5‐year overall survival (OS) and event‐free survival (EFS) of 95% and 69%, respectively. Conclusions: Chemotherapyis generally effective in malignant SC‐GCTs, even though almost one‐third of our patients experienced events salvageable with second‐line treatment. Most of the relapses occurred within 1 year from diagnosis. A close follow up with serial AFP level monitoring should be done for at least 2 years after diagnosis.